Peptidic defective interfering gene nanoparticles against Omicron, Delta SARS-CoV-2 variants and influenza A virus in vivo - Hanjun Zhao; Chuyuan Zhang; Hoiyan Lam; Xinjie Meng; Zheng Peng; Man Lung Yeung; Jasper Fuk-Woo Chan; Kelvin Kai-Wang To; Kwok-Yung Yuen (Signal Transduction and Targeted Therapy, 2022)
Abstract Defective interfering genes (DIGs) are short viral genomes and interfere with wild-type viral replication. Here, we demonstrate that the new designed SARS-CoV-2 DIG (CD3600) can significantly inhibit the replication of SARS-CoV-2 including Alpha, Delta, Kappa and Omicron variants in human HK-2 cells and influenza DIG (PAD4) can significantly inhibit influenza virus replication in human A549 cells. One dose of influenza DIGs prophylactically protects 90% mice from lethal challenge of A(H1N1)pdm09 virus and CD3600 inhibits SARS-CoV-2 replication in hamster lungs when DIGs are administrated to lungs one day before viral challenge. To further investigate the gene delivery vector in the respiratory tract, a peptidic TAT2-P1&LAH4, which can package genes to form small spherical nanoparticles with high endosomal escape ability, is demonstrated to dramatically increase gene expression in the lung airway. TAT2-P1&LAH4, with the dual-functional TAT2-P1 (gene-delivery and antiviral), can deliver CD3600 to significantly inhibit the replication of Delta and Omicron SARS-CoV-2 in hamster lungs. This peptide-based nanoparticle system can effectively transfect genes in lungs and deliver DIGs to inhibit SARS-CoV-2 variants and influenza virus in vivo, which provides the new insight into the drug delivery system for gene therapy against respiratory viruses.